Current financial control automation in a holding - O. D. Gaisha; V. A. Dzhioev; V. L. Okorokov (Вестник университета)
Financial control is critical to financial management at any level, ensuring the sound functioning of the system. Improvement of this function contributes to increase in efficiency of resource utilization and growth of speed of response to changes. The financial control organization aspects in such an integration form as a holding company have been studied. The issues faced by management companies of holdings when realizing the function of internal financial control have been determined. Based on the study results, an approach to current financial control automation in a holding company has been proposed: the algorithm of data collection and the format of its processing have been described, as well as approaches to automation of reporting forms for stakeholders in order to present the main trends and factors of deviations necessary for further management decisions. Practical significance of the study lies in the described approach accessibility in terms of the cost of its implementation and maintenance, as well as the maximum speed of data collection and processing in holdings with a branched structural organization. The research used bibliographic and logical analysis methods and a systematic approach.